PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE ROUNDTABLE UNTUK MENINGKATKAN KEMAMPUAN KOGNITIF FISIKA SISWA MAN 1 PEKANBARU PADA MATERI GERAK MELINGKAR - Helfi Susanti; Zulirfan '; M. Nor ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The purpose of this research is to investigate the improvement of physic achievement in physic learning by using roundtable strategy. Non – equivalent control group design has been used to find out the differentiate of physic achievement of both group, experiment group and control group. There were 57 students of MAN 1 Pekanbaru, class X that devide into two group, experiment and control have been participated in this research. The physic achievement test that consist of 25 items with multiple choice type was used. This instrument measure the physic achievement from C1 (knowledge) to C6 (evaluation) of Bloom Tacsonomy. The descriptive analysis found that physic achievement of students in roundtable learning is higher than conventional learning. The T-tes analysis showed that the differentiate of physic achievement of students was significant at 0,05 level.  Key Words :  physic achievement, physic learning, strategy roundtable